Acute passive stretching in a previously fatigued muscle: Electrical and mechanical response during tetanic stimulation - Esposito, F.; Ce, E.; Rampichini, S.; Veicsteinas, A. (Journal of Sports Sciences, 2009)
The aim of this study was to assess the effects of acute passive stretching on the electrical and mechanical response of a previously fatigued muscle. Eleven participants underwent maximal tetanic stimulations (50 Hz) of the medial gastrocnemius, before and after a fatiguing protocol and after a bout of passive stretching of the fatigued muscle. During contraction, surface electromyography (EMG), mechanomyography (MMG), and force were recorded. The following parameters were calculated: (1) the EMG root mean square (RMS), mean frequency, and fibre conduction velocity; (2) MMG peak-to-peak and RMS; (3) the peak force, contraction time, half-relaxation time, peak rate of force development (dF/dt) and its acceleration (d2F/dt2). Fatigue reduced peak force by 18% (P < 0.05) and affected the other force, EMG, and MMG parameters. After stretching: (1) all EMG parameters recovered to pre-fatigue values; (2) MMG peak-to-peak remained depressed, while RMS recovered to pre-fatigue values; (3) the peak force, peak rate of force development and its acceleration were further reduced by 22, 18, and 51%, respectively, and half-relaxation time by 40% (P < 0.05). In conclusion, acute passive stretching, when applied to a previously fatigued muscle, further depresses the maximum force-generating capacity. Although stretching does not alter the electrical parameters of the fatigued muscle, it does affect the mechanical behaviour of the muscle-tendon unit.